Evolutionary programming based technique for plug-in-hybrid electric vehicle charging system - Ahmad J.; Musirin I.; Zamani M.K.M.; Mustaffa S.A.S.; Aminuddin N.; Shaaya S.A.; Suyono H. (World Academy of Research in Science and Engineering, 2023)
In the era of millennium, the electric vehicle (EV) has a high demand from many sector which is to replace the existing internal combustion vehicle since it has given a negative side impacts towards the environment and also due to the increasing of the price of the fossil fuels that decreasing day by day. The electric vehicle is one of the alternative way to reduce pollution by moving the electric vehicle by using the energy that stored in the batterys car and after the battery has reach its limit, only then the petroleum will continue the role of the energy to move the electric vehicle. The energy that required by the batterys car are generated from the charging station which it connected to the distribution network. The charging or discharging of the electric vehicle could cause some power quality issues in a few terms such as voltage profile, power losses etc. This paper presents the Evolutionary Programming Based Technique for Plug-In-Hybrid Electric Vehicle Charging System. The proposal technique has been tested on the IEEE 33-bus distribution system. The results shown that the proposed technique managed to maximize the voltage level in the system in the plug-in-hybrid electric vehicle charging system environment. 2019, World Academy of Research in Science and Engineering. All rights reserved.